Genetic and Environmental Factors Affecting TNF-α Responses in Relation to Sudden Infant Death Syndrome - Moscovis, Sophia M.; Gordon, Ann E.; Al Madani, Osama M.; Gleeson, Maree; Scott, Rodney J.; Hall, Sharron T.; Burns, Christine; Blackwell, Caroline (Frontiers in Immunology, 2015)
Dysregulation of the inflammatory responses has been suggested to contribute to the events leading to sudden infant deaths. Our objectives were (1) to analyze a single nucleotide polymorphism (SNP) associated with high levels of tumor necrosis factor-α (TNF-α) responses, TNF G-308A, in sudden infant death syndrome (SIDS) infants, SIDS and control parents, and ethnic groups with different incidences of SIDS; (2) the effects of two risk factors for SIDS, cigarette smoke and virus infection, on TNF-α responses; and (3) to assess effects of genotype, cigarette smoke, and gender on TNF-α responses to bacterial toxins identified in SIDS infants. TNF G-308A genotypes were determined by real-time polymerase chain reaction for SIDS infants from Australia, Germany, and Hungary; parents of SIDS infants and their controls; and populations with high (Aboriginal Australian), medium (Caucasian), and low (Bangladeshi) SIDS incidences. Leukocytes from Caucasian donors were stimulated in vitro with endotoxin or toxic shock syndrome toxin-1 (TSST-1). TNF-α responses were measured by L929 bioassay (IU/ml) and assessed in relation to genotype, smoking status, and gender. There was a significantly higher proportion of the minor allele AA genotype among Australian SIDS infants (6/24, 24%) compared to 3/62 (4.8%) controls (p = 0.03). There were no significant differences in TNF-α responses by TNF G-308A genotypes when assessed in relation to smoking status or gender. Given the rarity of the TNF G-308A A allele in Caucasian populations, the finding that 24% of the Australian SIDS infants tested had this genotype requires further investigation and cautious interpretation. Although non-smokers with the AA genotype had higher TNFα responses to both TSST-1 and endotoxin, there were too few subjects with this rare allele to obtain statistically valid results. No effects of genotype, smoking, or gender were observed for TNF-α responses to these toxins.